The State, a Police Matter? What the Work of Internal Police Oversight Agencies Teaches Us about the State - Moreau de Bellaing, Cédric (SocietàMutamentoPolitica, 2021)
The stateness of the police institution is often assumed by social scientists. This article attempts to show that making that stateness uncertain may contribute to a renewal of the sociology of the State. Based on a fieldwork led on a French police internal affairs device, this article shows that its investigations concerning acts of violence and acts of what we will call “misuse of police authority” uncover the boundaries of police discretion. The analysis of the distribution of sanctions by police internal affairs units permits the author to explore a sociology of trials in the State, that is to say of moments in which police stateness is experienced.